Mengoptimalkan Kesehatan Mental di Era Digital: Tips dan Trik - af’idah, maslama nur (Maliki Interdisciplinary Journal, 2024)
Advances in digital technology have had a major impact on modern life, including mental health. Although technology makes many things easier, dependence on digital devices and excessive use of social media can cause negative impacts such as anxiety, stress and sleep disorders. This paper discusses various ways to maintain and improve mental health in the digital era through a number of tips and tricks that can be applied in everyday life. Some of the proposed methods include limiting time for technology use, managing social media consumption, implementing digital detox, and practicing mindfulness and meditation. in addition, attention to quality sleep and a regular exercise routine are also emphasized to support overall mental health. With the right approach in using technology, we can create a balance between the virtual world and the real world, and maintain mental health amidst the rapid development of technology.